Hydrodynamic coefficients from forced and decay heave motion tests of a scaled model of a column of a floating wind turbine equipped with a heave plate. (15th May 2022) - Medina-Manuel, Antonio; Botia-Vera, Elkin; Saettone, Simone; Calderon-Sanchez, Javier; Bulian, Gabriele; Souto-Iglesias, Antonio
Abstract: This paper describes the results of an experimental campaign aimed at the determination of heave hydrodynamic coefficients for a column of a floating wind turbine platform, equipped with a solid heave plate. The tests are carried out with an experimental system that allows performing both heave forced oscillation tests and heave decay tests. A specific characteristic of the system is the reduced mechanical friction, thanks to the use of air bushings. A series of forced oscillation and decay experiments have been carried out with such a model, and the hydrodynamic coefficients obtained in both types of tests are compared. Results show correlation between both methods if the mean of the peaks of the decay process is chosen to represent its Keulegan–Carpenter number ( K C ), with a fair matching of the results in the K C range where both methods are applicable. With the objective of conducting an uncertainty assessment which can be relevant for the full-scale extrapolation of results, non-dimensional added mass and damping coefficients are proposed. They incorporate the primitive relevant variables and are shown to lead to a notable collapse of the various results in the form of curves with small differences among them. With these coefficients, an uncertainty assessment is carried out, propagating to those coefficients the uncertainties of the primitive variables in place. Such non-dimensional coefficients are useful to develop simple models to estimate the dimensional ones to be used in numerical simulations of the full scale system. The estimated uncertainties can serve to define design safety margins for the values of such coefficients. Highlights: A novel device for conducting heave forced oscillation and decay tests is presented. A model of a leg of a floating wind turbine, with a solid heave plate, has been tested. A significant correlation of the hydrodynamic coefficients from both methods has been found. Non-dimensional added mass and damping coefficients are proposed. They have been used for uncertainty assessment and results extrapolation.